Um estudo da arte-sequencial: os componentes imagéticos e textuais em homem-aranha : azul - Castro, Johannes Kennis Fontes de Moraes e [UNESP] (2015)
Comic books, graphic narrative and sequential art, had their origin in newspapers, in the period of the Industrial Revolution. First published weekly in the comic strip format, with the passage of time, the new form of literature has gained more and more public and comic strips became complete stories in the format of comic books and later, graphic novels. This course's final paper aims to present the main components of comics: the picture and the text; and to examine the way in which these two elements overlap and complement each other in the configuration of comics as a whole. As the object of analysis, it was chosen the graphic novel Spider-Man: Blue, first published in 2002 as part of a project composed by three other titles from the double winning cartoonists of the Eisner Award, Jeph Loeb and Tim Sale. For theoretical background, was chosen the book Os Quadrinhos - Linguagem e Semiótica: Um Estudo Abrangente da Arte Sequencial written by the researcher Antonio Luiz Cagnin, which presents a study of all components found in the sequential art and treated in this work: the narrative time, visual plans, balloons, caption, and onomatopoeia